Exploring the comparative genome of rice pathogen Burkholderia plantarii: unveiling virulence, fitness traits, and a potential type III secretion system effector - Mannaa, Mohamed; Lee, Duyoung; Lee, Hyun-Hee; Han, Gil; Kang, Minhee; Kim, Tae-Jin; Park, Jungwook; Seo, Young-Su (Frontiers in Plant Science, 2024)
This study presents a comprehensive genomic analysis of Burkholderia plantarii, a rice pathogen that causes blight and grain rot in seedlings. The entire genome of B. plantarii KACC 18964 was sequenced, followed by a comparative genomic analysis with other available genomes to gain insights into its virulence, fitness, and interactions with rice. Multiple secondary metabolite gene clusters were identified. Among these, 12 demonstrated varying similarity levels to known clusters linked to bioactive compounds, whereas eight exhibited no similarity, indicating B. plantarii as a source of potentially novel secondary metabolites. Notably, the genes responsible for tropolone and quorum sensing were conserved across the examined genomes. Additionally, B. plantarii was observed to possess three complete CRISPR systems and a range of secretion systems, exhibiting minor variations among the analyzed genomes. Genomic islands were analyzed across the four genomes, and a detailed study of the B. plantarii KACC 18964 genome revealed 59 unique islands. These islands were thoroughly investigated for their gene contents and potential roles in virulence. Particular attention has been devoted to the Type III secretion system (T3SS), a crucial virulence factor. An in silico analysis of potential T3SS effectors identified a conserved gene, aroA. Further mutational studies, in planta and in vitro analyses validated the association between aroA and virulence in rice. Overall, this study enriches our understanding of the genomic basis of B. plantarii pathogenicity and emphasizes the potential role of aroA in virulence. This understanding may guide the development of effective disease management strategies.